Gel permeation chromatography as a multifunctional processor for nanocrystal purification and on-column ligand exchange chemistry. Issue 9 (2nd June 2016) - Shen, Yi; Roberge, Adam; Tan, Rui; Gee, Megan Y.; Gary, Dylan C.; Huang, Yucheng; Blom, Douglas A.; Benicewicz, Brian C.; Cossairt, Brandi M.; Greytak, Andrew B.
Abstract : GPC provides a general approach to purification of a variety of nanocrystal types, and additionally achieves ligand exchange in a continuous flow system. Abstract : This article illustrates the use of gel permeation chromatography (GPC, organic-phase size exclusion chromatography) to separate nanocrystals from weakly-bound small molecules, including solvent, on the basis of size. A variety of colloidal inorganic nanocrystals of different size, shape, composition, and surface termination are shown to yield purified samples with greatly reduced impurity concentrations. Additionally, the method is shown to be useful in achieving a change of solvent without requiring precipitation of the nanocrystals. By taking advantage of the different rates at which small molecules and nanoparticles travel through the column, we show that it is furthermore possible to use the GPC column as a multi-functional flow reactor that can accomplish in sequence the steps of initial purification, ligand exchange with controlled reactant concentration and interaction time, and subsequent cleanup without requiring a change of phase. This example of process intensification via GPC is shown to yield nearly complete displacement of the initial surface ligand population upon reaction with small molecule and macromolecular reactants to form ligand-exchanged nanocrystal products.